2018
DOI: 10.3892/mmr.2018.8910
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‑145 modulates migration and invasion of bladder cancer cells by targeting N‑cadherin

Abstract: MicroRNA (miRNA)‑145 has been demonstrated to serve a role in several types of tumors, however, the potential molecular mechanism of action of miRNA‑145 in bladder cancer metastasis remains to be elucidated. This study aimed to investigate the potential modulation of miRNA‑145 in bladder carcinoma and elucidate the underlying molecular mechanism. The expression of miRNA‑145 in bladder adenocarcinoma tissues and bladder cancer cells was measured by reverse transcription‑quantitative polymerase chain reaction. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…Studies have shown a reduced level of this miRNA in cells and tissues of patients with bladder cancer as compared to the control group. [38] Similar observations were noted in our study, however, on other biological material. We also found that the relative expression levels of miRNA 145-3p in urine of patients suffering from BCa was reduced.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown a reduced level of this miRNA in cells and tissues of patients with bladder cancer as compared to the control group. [38] Similar observations were noted in our study, however, on other biological material. We also found that the relative expression levels of miRNA 145-3p in urine of patients suffering from BCa was reduced.…”
Section: Discussionsupporting
confidence: 92%
“…In prostate cancer, ZEB2 was shown to be involved in a double negative feedback loop with miR-145 [81], and indeed ZEB2 and miR-145 levels are negatively correlated in prostate cancers. Moreover, miR-145 overexpression in DU145 prostate cancer cells could downregulate the mesenchymal markers N-CADHERIN, VIMENTIN and FIBRONECTIN while increasing E-CADHERIN levels [81,82]. Similar results were obtained in PC3 prostate cancer cells by Peng and colleagues, who showed that miR-143 and -145 levels were lower in samples from bone metastatic lesions that in primary prostate cancers, suggesting that their downregulation might help cells to undergo EMT and escape from the primary site [83].…”
Section: Mir-143 and -145 And Emtsupporting
confidence: 71%
“…The dysregulation of miRNA-145 expression has been reported in different types of cancers. In bladder cancer and lung cancer, miRNA-145 inhibits migration and invasion of tumor cells by directly targeting N-cadherin [12,13]. In the present study, we found that the expression of miRNA-145 was down-regulated in PC tissues comparing to the paired adjacent no cancerous tissues.…”
Section: Discussionsupporting
confidence: 53%
“…Studies showed that miR-145 was capable of binding to the 3'-UTR of SMAD3, thereby inhibiting its protein expression and subsequent inhibiting the transforming growth factor beta (TGF-β)-induced epithelial to mesenchymal transition (EMT) [10,11]. However, miR-145 could promote the EMT in human peritoneal mesothelial cells by restraining the fibroblast growth factor 10 [12]. The mechanism of miR-145 needs to be elucidated in the EMT process.…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation